Forest Management in the Interface: Reducing Fire Risk - Bruce Hull; Raelene Crandall; Sarah Ashton; Rien Visser; Martha Monroe (EDIS)
Managing wildfire in the wildland-urban interface (WUI) is challenging. Maintaining community preparedness is a crucial step in mitigating wildfire risk. Wise management of vegetation in and around communities, including procedures such as mechanical fuel reduction, herbiciding, and prescribed fire can be used to keep fuel loads low and increase the safety of developments in fire-prone areas. Using fire-resistant materials for building construction and landscaping with firewise plants are also important steps to decrease wildfire risk.